2019
DOI: 10.1029/2019wr025264
|View full text |Cite
|
Sign up to set email alerts
|

Three‐Phase Fractional‐Flow Theory of Foam‐Oil Displacement in Porous Media With Multiple Steady States

Abstract: Understanding the interplay of foam and nonaqueous phases in porous media is key to improving the design of foam for enhanced oil recovery and remediation of aquifers and soils. A widely used implicit-texture foam model predicts phenomena analogous to cusp catastrophe theory: The surface describing foam apparent viscosity as a function of fractional flows folds backwards on itself. Thus, there are multiple steady states fitting the same injection condition J defined by the injected fractional flows. Numerical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 77 publications
0
6
0
Order By: Relevance
“…The effect of crude oil on foam simulation has been extensively simulated using the fractional flow theory, 47 , 61 63 PB foam model, 64 and LE foam model. 33 , 46 In this section, the effect of oil on foam strength is evaluated by a simplified STARS foam model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of crude oil on foam simulation has been extensively simulated using the fractional flow theory, 47 , 61 63 PB foam model, 64 and LE foam model. 33 , 46 In this section, the effect of oil on foam strength is evaluated by a simplified STARS foam model.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of crude oil on foam simulation has been extensively simulated using the fractional flow theory, , PB foam model, and LE foam model. , In this section, the effect of oil on foam strength is evaluated by a simplified STARS foam model. Figure summarizes the effect of oil on steady-state foam PG by a so-called wet-foam model. , Only the foam mobility reduction factor (FM) is modified in the calculation, as described in eqs and .…”
Section: Discussionmentioning
confidence: 99%
“…Other cases where the universal solution behaviour is observed are reported in [1,24,36,44,48,55] as well as for the injection of CO 2 and CH 4 in NOTT-400 nanotubes, [25]. Moreover, preliminary results show that the universal solution behaviour persists for SAG injection (surfactant alternating gas) in the presence and absence of foam, see [35,46,53].…”
Section: Introductionmentioning
confidence: 85%
“…It is reported that the foam strength in porous media is largely influenced by the surfactant type and concentration, reservoir property (salinity, hardness, temperature, wettability, oil saturation, permeability, heterogeneity, etc. ), operational methods (flow rate, injection scheme, foam quality, etc. ), , gas type, local capillary pressure, and foam texture. Note that the foam steady state may indicate a balance between the lamellae creation rate and lamellae coalescence rate.…”
Section: Introductionmentioning
confidence: 99%
“…It is universally accepted that oil has a detrimental effect on the foam stability, especially when the oil sample contains a large amount of light components. ,, The destabilization effect of oil on the foam stability has been extensively investigated, and several criteria have been proposed to predict the stability of foam in the presence of oil. Among them, the most reliable theory may be based on the stability of the pseudoemulsion film, i.e., the pseudoemulsion film disjoining pressure. , The other theories to account for the oil destabilization effect include lamellae number and the entering/spreading/bridging coefficients, which are calculated based on the surface/interfacial tension .…”
Section: Introductionmentioning
confidence: 99%